Investigating the practice of teachers' leadership skills and its correlation with students' academic optimism in basic and post-basic education schools in two selected governorates in the Sultanate of Oman - Al Saidi, Jawahir Ali Khamis (Kulliyyah of Education, International Islamic University Malaysia, 2022)
The purpose of the study was to investigate the practice of teachers’leadership skills and its correlation with students’ academic optimism in basic and post basic school in selected governorates in the Sultanate of Oman. The study had administered a set of survey questionnaires among 316 teachers with 10 or more years of teaching experience from schools in Al Batinah- North and Al Batinah -South Governorates in Oman. The study employed descriptive statistics, ANNOVA, t-tests and Pearson correlation to address the research questions. It was found that expertise factor was the most dominant leadership skill practiced by the teachers but varied according to experience and age group, but not qualification and gender. Interestingly, the most dominant academic optimism dimension perceived by the respondents was students' trust in teachers but differed significantly by experience, but not by gender, qualification, age group or governorates. In addition, there was strong evidence of statistically significant positive relationship between leadership skills of teachers and students’ academic optimism. Theoretically, the study found that not only leadership practices perspectives are requiring investigation and it also needs to know which type of leadership skill is required by teachers to increase their leadership ability and their understanding of the implications of practicing effective leadership, particularly the impact of such leadership on students’ academic optimism. As this is the first research of its kind in Oman, its value will be important for students’ growth academically and provides a basis for future studies as well, particularly in the Omani context. This study has obviously contributed to the body of knowledge in this field, closed the gap in the literature of educational leadership in Omani context and it served as improvement and awareness for the Ministry of Education, Oman.